Sulforaphane as a potential modifier of calorie-induced inflammation: a double-blind, placebo-controlled, crossover trial - van Steenwijk, Hidde P.; Vinken, Anna; van Osch, Frits H. M.; Peppelenbos, Herman; Troost, Freddy J.; Bast, Aalt; Semen, Khrystyna O.; de Boer, Alie (Frontiers in Nutrition, 2023)
Background & Aims: Observational data indicate that diets rich in fruits and vegetables have a positive effect on inflammatory status, improve metabolic resilience and may protect against the development of non-communicable diseases. Nevertheless, experimental evidence demonstrating a causal relationship between nutrient intake (especially whole foods) and changes in metabolic health is scarce. This study investigated the pleiotropic effects of sulforaphane from broccoli sprouts, compared to pea sprouts, on biomarkers of endothelial function, inflammation and metabolic stress in healthy participants subjected to a standardized caloric challenge.In this double-blind, crossover, randomized, placebo-controlled trial twelve healthy participants were administered 16 g broccoli sprouts, or pea sprouts (placebo) followed by the standardized high-caloric drink PhenFlex given to disturb healthy homeostasis. Levels of inflammatory biomarkers and metabolic parameters were measured in plasma before and two hours after the caloric overload.Results: Administration of broccoli sprouts promoted an increase in levels of CCL-2 induced by caloric load (p = 0.017). Other biomarkers (sICAM-1, sVCAM-1, hs-CRP, and IL-10) individually showed insignificant tendencies towards increase with administration of sulforaphane. Combining all studied biomarkers into the systemic low-grade inflammation score further confirmed upregulation of the inflammatory activity (p=0.087) after sulforaphane. No significant effects on biomarkers of metabolic stress were detected.This study has demonstrated that sulforaphane facilitated development of a mild proinflammatory state during the caloric challenge, which could be suggestive of the onset of the hormetic response induced by this phytonutrient. The use of integrative outcomes measures such as the systemic low-grade inflammation score can be viewed as a more robust approach to study the subtle and pleiotropic effects of phytonutrients.